At Home in Zulu and English: RRR Dhlomo's Imaginative Writing. Issue 1 (2nd January 2021) - Sithole, Nkosinathi
Abstract : While RRR Dhlomo (Rolfes Robert Reginald Dhlomo) is known for being the first black South African to publish a novella in English, An African Tragedy (1928), and for having published English short stories in Sjambok and The Bantu World in the late 1920s and early 1930s, he made a greater impact on isiZulu literature as a historical and fictional novelist. In this essay I am concerned with Dhlomo's fictional writing in English and isiZulu, exploring his development as a writer not only of An African Tragedy and the short stories in Sjambok and The Bantu World but also of his isiZulu novel, Indlela Yababi (The Path of the Wicked) (1946). I argue that Indlela Yababi is the development or revision of An African Tragedy even though it is written in a different language, his mother tongue, uses different characters, and the situation is somewhat altered. Dhlomo's writing engages with the plight of black people in South Africa from the 1920s to the 1940s, looking mainly at the impact of urbanisation and the state's urban control laws. Because he keeps revisiting certain significant issues in his writing, reading his English and isiZulu writing is more illuminating and rewarding.